Perubahan NIlai pH Media Cair Daerah Permukaan Leher Gigi Pada Perawatan Bleaching Intra Korona - Kamizar Kamizar; Siti Mardewi Soerono Akbar; Winiarti Sidharta (Faculty of Dentistry, Universitas Indonesia, 2015)
Intra coronal bleaching treatment can cause penetration of bleaching materials into the cervical teeth surface and due to this penetration the pH range would change around these area. From this point the research started by arranging 3 types of bleaching materials i.e. mixture of sodium perborat with water, sodium perborat with H2O2 3% and sodium perborat with H2O2 30%. These bleaching component were conditioned into the pulp 2 mm under cemento enamel junction on the trial tooth whose roots had been filled in, after that it was covered up with zinc phosphat cement and above this paraffin wax and nail. The removed tooth was soaked in a aquabides bottle and pH value was measured from the first day, third and seventh. Result showed that there was a change of pH in the aquabidest. The change appeared firstly on the first day with various levels on each group. Sod. Perborat + H2O2 3% to 7,84 and with water 8,015. As a matter of fact on the third day the change happened to sod. Perborat with water 8,037 and 8,298 with H2O2 3% 8,732 and 8,750. While sod. perborat with H2O2 30% was felt down its concentration into 8,847 and 8,827. As a result the change aquabidest pH was interfered or depended on the mixture of the bleaching materials itself such as; so. Perborat with water=10,15 ; sod. perborat with H2O2 3%= 9,10; sod. perborat with H2O2 30%= 7,60. pH value sod. perborat with water on the seventh day showed up its raising action though it's still below the rest two other groups' concentration pH levels.